SCREENING OF PHYTOCHEMICAL, ANTIOXIDANT ACTIVITY AND ANTI-BACTERIAL ACTIVITY OF MARINE SEAWEEDS - T., Rajasekar; A., Mary Shamya; Joseph, Jerrine (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: Phytochemical is naturally present in the seaweeds which biologically play a significant role. The intention of this study was designed to screen the phytochemical constituents and antimicrobial potential of selected seaweed collected from Rameshwaram and Tuticorin Southern coast of India. Methods: The present study investigated the presence of phytochemical constituents and also total phenol, total carbohydrate and total protein quantity of the brown seaweed. Dictyopteris delicatula, Padina gymnospora, Acanthophora spicifera, Portieria hornemannii and Ulva faciata were extracted with solvents having different polarities like methanol, ethanol, chloroform and water and screened for the phytochemical constituents, total phenol, total carbohydrate, total protein and DPPH with standard procedure. The antibacterial activities of the seaweeds were examined by agar well diffusion method. Results: Among the five seaweeds, U. faciata showed the maximum number of active constituents in the methanol extract likewise P. gymnospora was found to have a number of diligent compounds in ethanol extract. A. spicifera showed minimum compounds in ethanol as well as chloroform extract. Moreover A. spicifera, P. hornemannii have shown the superior quantity of protein and carbohydrate when compared to other species. The scavenging activity of methanol extracts at 5 mg/ml concentration P. hornemannii shows 18.2% and A. spicifera possess 17.1%. In the antibacterial activity, methanol extracts of all the seaweed showed a potential inhibitory activity against B. cereus and P. aeruginosa compared to other pathogens. Conclusion: The crude extract of seaweed manifest preferable antimicrobial and antioxidant activities, hence in the future, it would be good if it is further taken for treatment of human diseases or as new antimicrobial agents to replace synthetic antimicrobial agents.